COMMUNICATION AND SERVICE TO THE PUBLIC: the use of the Internet and mobile applications to raise the level of services and strengthen the relationship between people and government organizations - Caio de Matos, Lucas; Del Vechio, Gustavo Henrique (Revista Interface Tecnológica, 2020)
Much more than just informing about actions, products and services, organizations, whether private or public, must know how to communicate with their stakeholders. In this way, this study seeks to evaluate the benefits in the communication process, especially in view of the continuous growth of the digital universe, use of mobile devices and social media. To verify the relevance of these concepts, the study presents the case of the Municipality of Santo André / SP, a public agency that recently decided to invest in improvements in the relationship with citizens, replacing its manual service flow with an integrated and automated system capable of facilitating considerably the contact between citizens and sectors of activity, both for them to communicate and to open new calls, with a view to solving problems in their neighborhoods. What can be seen from this study is that the more organizations know how to communicate, the more they can gain advantages in terms of proximity and long-term relationships with stakeholders.
Keywords: Communication; Information; Public administration; Relationship